Co-creating Digital Stories With UK-Based Stroke Survivors With the Aim of Synthesizing Collective Lessons From Individual Experiences of Interacting With Healthcare Professionals - Hall, Joseph; Kroll, Thilo; van Wijck, Frederike; Bassil-Morozow, Helena (Frontiers in Rehabilitation Sciences, 2022)
Background: Stroke survivor narratives can provide valuable insight into experiences of healthcare and beyond. There is need to further understand collective lessons from stroke survivor narratives, yet prior studies utilising digital storytelling tend to not synthesise lessons from individual experiences. This study aims to develop a novel method to co-create digital stories with stroke survivors that will aim to synthesise important collective lessons from individual stroke survivors’ experiences of interacting with healthcare professionals. Methods: This study follows-up a qualitative study conducted with 30 stroke survivors exploring factors that help or hinder survivors to positively reconfigure their identity post-stroke. Five co-creation workshops were conducted with a subset of UK-based stroke survivors from this previous study. Participants were invited to join through: online workshops, an online bulletin board, and as an advisor. A four-stage workshop framework was developed through the integration of UK Design Council’s Double Diamond method, digital storytelling strategies and the Behaviour Change Wheel (BCW) framework for developing behavioural change interventions. Findings: Six online workshop participants (3 male, 3 female; aged 33-63; time since stroke 2-16 years) co-created digital stories that share six collective lessons aimed at increasing empathy and encouraging behaviour change in healthcare professionals (HCPs) working with stroke survivors. Online bulletin board participants (n = 1) and advisors (n = 5) supported the co-creation process. Collective lessons identified were: 1) Stroke has a variety of symptoms that must all be considered; 2) Stroke can affect anyone of any age and not just the elderly; 3) Assumptions should not be made about a survivor’s lifestyle or habits; 4) It is important to acknowledge the person behind the stroke and ensure that they are communicated with and listened to; 5) Stroke survivors can often feel unprepared for the reality of life after stroke; 6) Adapting to life after stroke is a long-term process requiring long-term support. Conclusion: Stroke survivor stories highlighted preconceptions, attitudes and behaviours embedded within healthcare that negatively impacted their experiences and recovery. The novel methodology employed in this study enabled these stories to be synthesised into collective lessons to bring about improvements in these behaviours in future.